PERBEDAAN KOMPETENSI INTERPERSONAL ANTARA SISWA YANG MENGIKUTI PROGRAM PERCEPATAN BELAJAR DENGAN SISWA YANG MENGIKUTI KELAS REGULER - Eka Danta Jaya Ginting (Universitas Negeri Yogyakarta, 2005)
Abstract The aim of this study was to investigate the difference of interpersonal competence between student in acceleration program and regular program in high school. This research was field study in which data collected using Interpersonal Competence Scale. Subject were 150 students of SMUN 1 Medan, SMUS Sutomo Medan, and SMUS Muhammadiyah Plus Medan. Analysis of Variance shows a difference between acceleration and regular program in interpersonal competence(t=4.656; p 0.01) and students in acceleration program have interpersonal competence lower than the students of regular program (Xacceleration = 152.27 and Xregular= 168.67). In addition, results show the existence of difference of interpersonal competence in genre, organization activity and students and place. Keywords: interpersonal competence, acceleration program and regular program